Quotient of cerebrospinal fluid/serum immunoglobulin G as a predictive factor for non‐responders to intravenous methylprednisolone therapy in patients with relapsing neuromyelitis optica spectrum disorder: Implication for early initiation of plasmapheresis. Issue 3 (31st July 2016) - Oji, Satoru; Tanaka, Satoru; Kojima, Miki; Fukaura, Hikoaki; Mori, Masahiro; Takahashi, Toshiyuki; Fujihara, Kazuo; Nomura, Kyoichi
Abstract: Objectives: We aimed to determine the predictive factors for the ineffectiveness of intravenous methylprednisolone (IVMP) that lead to earlier use of plasmapheresis in patients with relapsing neuromyelitis optica spectrum disorder. Methods: A total of 40 patients were investigated retrospectively. The responders were defined as patients who showed IVMP effectiveness within 7 days from IVMP initiation, indicated by an improvement in the Kurtzke Expanded Disability Status Scale (EDSS) ≥0.5, whereas non‐responders were defined as those without such an improvement. We analyzed 10 clinical findings and four cerebrospinal fluid (CSF) parameters before IVMP, which included EDSS (baseline before relapse, before IVMP initiation, difference between them: ΔEDSS), CSF‐cells, CSF‐lactate dehydrogenase, CSF/serum quotient of albumin (Q‐ALB) and immunoglobulin G (Q‐IgG). Results: The 40 patients consisted of 22 responders and 18 non‐responders. The levels of ΔEDSS, EDSS before IVMP, CSF‐cells, CSF‐lactate dehydrogenase, Q‐ALB and Q‐IgG were significantly higher in non‐responders than in responders. Of these, univariate logistic regression analyses showed that the ΔEDSS, EDSS before IVMP, Q‐ALB and Q‐IgG were significantly related to IVMP ineffectiveness. Because of the significant correlation between ΔEDSS and EDSS before IVMP, and between Q‐ALB and Q‐IgG, the ΔEDSS and Q‐IgG were analyzed as dependent factors for IVMP ineffectiveness in multivariate analysis. The higher Q‐IgG level was found to be independently associated with ineffectiveness. The cut‐off level for Q‐IgG to discriminate non‐responders from responders was 4.7 (sensitivity 83, specificity 91%). Conclusions: Q‐IgG >4.7 before IVMP is a predictive factor for IVMP ineffectiveness. Early use of plasmapheresis should be considered in relapsing neuromyelitis optica spectrum disorder with such high Q‐IgG values before IVMP. Abstract : The prediction of non‐responders to intravenous methylpredonisolone therapy (IVMP) contributes to earlier intervention with plasmapheresis (PP) which produces better clinical outcome in patients with relapsing neuromyelitis optica spectrum disorder (NMOSD). Quotient of cerebrospinal fluid/serum (Q‐IgG) >4.7 before IVMP administration was found to be an independent predicting factor for IVMP ineffectiveness. Our finding provided a suggestion that early institution of PP should be considered in relapsing NMOSD patients who showed such high Q‐IgG values before IVMP.